Competitiveness of the Selected Countries of the EU with a Focus on the Quality of the Business Environment - Zuzana Hajduova; Jana Coronicova Hurajova; Marian Smorada; Ludovit Srenkel (Journal of Competitiveness, 2021)
The business environment and entrepreneurship are important elements in the economic growth of each country. The better the business environment a given country offers, the more attractive the country is for small and large companies as well as for private entrepreneurs. A high level of business competitiveness can help a country secure economic growth, especially after overcoming a crisis such as the COVID-19 pandemic. Many institutions focus on the measurement of the business environment using indices to evaluate its quality. The main goal of the present study is to evaluate the quality of the business environment through multicriteria analysis. For the period from 2018 to 2020, the data were analysed by using seven selected indices of the weighted sum approach (WSA) and the technique for order preference by similarity to ideal solution (TOPSIS) methods. The research sample included all EU countries that joined the EU at the same time in 2004. The processing of analytical data was gradually implemented by using descriptive statistics and multicriteria evaluation methods. The methods used in the multicriteria evaluation of variants determined the rankings of the individual variants in terms of the selected criteria using entropy. We concluded that the efficiency of the business environments in Cyprus, the Czech Republic, Estonia, Hungary, Poland, Latvia, Lithuania, Slovakia and Slovenia are below the EU average. Within this group of countries, Estonia, Malta and Slovenia have seen the largest regeneration of their business environment since having joined the EU.